2017
DOI: 10.1016/j.ymgmr.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Case report of treatment experience with idursulfase beta (Hunterase) in an adolescent patient with MPS II

Abstract: Mucopolysaccharidosis (MPS) II or Hunter syndrome is a chronic, progressive, multi-systemic illness associated with significant morbidity and early mortality. Available evidence in Asian populations shows that Hunter syndrome has a mean age of onset of 2 to 5 years and a life expectancy of 13 years in more severely affected individuals, with respiratory failure reported as the leading cause of death. Enzyme replacement therapy (ERT) with idursulfase (Elaprase, Shire Pharmaceuticals) and idursulfase beta (Hunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
0
10
0
5
Order By: Relevance
“…In addition, all but one patient had a greater increase in DA at week 100 compared with historical controls, with an average difference for all six patients of +5.1 months. Thus, unlike intravenously administered idursulfase and idursulfase beta, which cannot penetrate the blood-brain barrier, 1 , 12 i.c.v. administration of idursulfase beta may be expected to improve CNS manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all but one patient had a greater increase in DA at week 100 compared with historical controls, with an average difference for all six patients of +5.1 months. Thus, unlike intravenously administered idursulfase and idursulfase beta, which cannot penetrate the blood-brain barrier, 1 , 12 i.c.v. administration of idursulfase beta may be expected to improve CNS manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in 2017 by Ngu and colleagues indicated high MPS II type frequency. Out of 79 MPS patients, a total of 30 patients were identified as MPS II [ 28 ].…”
Section: Updated Epidemiology Of Mps In the Seven Countriesmentioning
confidence: 99%
“…Пациентам может потребоваться удлинение времени инфузии и/или приостановка введения препарата из-за развития нежелательных реакций [10][11][12], наиболее частыми из которых являются реакции гиперчувствительности [10][11][12], которые обычно купируются путем замедления скорости инфузии и проведения премедикации антигистаминными препаратами и/или антипиретиками (парацетамол или ибупрофен). Однако в ряде случаев побочные эффекты ФЗТ не поддаются контролю и могут значительно осложнять лечение [18]. В связи с этим целесообразным представляется переключение с одного препарата для ФЗТ на другой [18].…”
Section: вопросы современной педиатрииunclassified
“…Однако в ряде случаев побочные эффекты ФЗТ не поддаются контролю и могут значительно осложнять лечение [18]. В связи с этим целесообразным представляется переключение с одного препарата для ФЗТ на другой [18].…”
Section: вопросы современной педиатрииunclassified